Structural development of a novel punctually supported timber building system for multi-storey construction. (15th October 2022) - Krtschil, Anna; Orozco, Luis; Bechert, Simon; Wagner, Hans Jakob; Amtsberg, Felix; Chen, Tzu-Ying; Shah, Anand; Menges, Achim; Knippers, Jan
Abstract: Though capable of allowing multi-directional spans, timber products such as cross-laminated timber are primarily utilized uni-directionally using linear supports like walls or beam elements. Recent building designs increasingly show punctual supports but with narrow column grid layouts. Support beams and narrow grids limit the design space for multi-storey timber buildings. To overcome these design limits, an integrative design concept for punctually supported timber slabs is being developed that allows for large spans and irregular column layouts. Therefore, engineering methods are integrated in the architectural design of the building components, such as plates, columns, and their connections. The developed slab system combines hardwood and softwood materials in a sandwich construction. The plates have a tailored internal topology considering the force flow in the slab. A plate-to-plate connection design is evaluated through mechanical tests, which also serve as calibration for the global structural model. The research findings are validated through the design and construction of a large scale demonstrator: the ITECH Campus Lab. Graphical abstract: